ChemInform Abstract: Dehydrogenative N‐Incorporation: A Direct Approach to Quinoxaline N‐Oxides under Mild Conditions. Issue 11 (March 2015) - Chen, Feng; Huang, Xiaoqiang; Li, Xinyao; Shen, Tao; Zou, Miancheng; Jiao, Ning
Abstract A one‐pot method starting from anisidine (XI) and acetophenone (XII) is also demonstrated.